2014
DOI: 10.1108/jfmm-09-2011-0059
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade strategies in the Thai silk industry: balancing value promotion and cultural heritage

Abstract: Purpose – The purpose of this paper is to substantiate Porter's ideas through multiple case studies of firms in one of Thailand's potential niches – Thai silk. Design/methodology/approach – This study examined upgrading strategies adopted by six companies involved in the production and distribution of silk and silk products in Thailand. Information was gathered from company documents and interview statements given by company executives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The abovementioned problems have commanded the attention of some researchers, for example, (Fayaz & Azizinia, 2016;Herhausen et al, 2015;Kluge & Fassnacht, 2015;Patichol et al, 2014;Menon Vadakepat & Al Khateeb, 2012), who studied the challenges of different distribution channels for creative products with special features, including how these are affected by changes in consumers' behaviors due to advances in digital technology. Moreover, garments made from hand-woven fabrics need to be touched and tried on by the customer before any purchasing decision is made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abovementioned problems have commanded the attention of some researchers, for example, (Fayaz & Azizinia, 2016;Herhausen et al, 2015;Kluge & Fassnacht, 2015;Patichol et al, 2014;Menon Vadakepat & Al Khateeb, 2012), who studied the challenges of different distribution channels for creative products with special features, including how these are affected by changes in consumers' behaviors due to advances in digital technology. Moreover, garments made from hand-woven fabrics need to be touched and tried on by the customer before any purchasing decision is made.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found a number of limitations in the means traditionally adopted in marketing the products of local weaving CEs (Fayaz & Azizinia, 2016;Herhausen et al, 2015;Kluge & Fassnacht, 2015;Patichol et al, 2014;Menon Vadakepat & Al Khateeb, 2012). The distribution channels are rather limited and traditionally, only physical distribution channels were employed.…”
Section: Thai Weaving Community Enterprises As Creative Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While some craft productsespecially in the domain of food and beveragehave become highly popular even outside their original cultural boundaries, others may require some degree of cultural knowledge to facilitate aesthetic appreciation (Jenkins, 1978;Kida & Takayama, 2010) or to recognize their cultural significance (Micelli & Sacchetti, 2014;Patichol et al, 2014). As our cases also illustrate, in the absence of this knowledge, foreign customers may be reluctant to pay the premium price often associated with the quality materials and the labour-intensive, small-scale production that characterizes these products.…”
Section: Methodsmentioning
confidence: 99%
“…Diligent commitment to local traditions and social pressure in the local community may secure some producers a premium position in foreign markets, to the extent that they manage to build a distinctive collective reputation for the country (Arikan et al, 2019;Bertacchini & Borrione, 2013) or region of origin (Ger, 2000;Guy, 2002). In the absence of this effect, however, cultural embeddedness may effectively hamper the capacity of a producer to adapt its offering in an early stage of their internationalization process, when, because of cultural specificity, some degree of detachment from the home culture may be important to meet foreign tastes (Fan & Tan, 2015;Patichol, Wongsurawat & Johri, 2014) and accommodate expectations in host countries (Asakawa et al, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%